E-LEARNING: CURRENT STATE OF PROBLEM IN HIGHER EDUCATION SYSTEM OF RUSSIA AND FOREIGN COUNTRIES - T. M. Shkapenko (Vestnik MGIMO-Universiteta)
The development level of e-learning in Russian, European and American universities is analyzed in the paper on the basis of latest statistic data. Russian system of education is standing behind western countries in this field. The reasons for this are characterized in this paper, and the necessity of accelerated introduction of e-learning as the means of survival and preservation of competitiveness of national system of education is argued.The author believes that in the era of open knowledge society, when different universities offer distant education allowing to study without leaving house, the introduction of e-learning is the only way to fight for survival of national system of education. Therefore universities in different countries pool their intellectual and financial resources in order to gain their own niche in the market of cross-border education. The author comes to conclusion that in the situation, when Russia is threatened with not only real but virtual outflow of students as well, we have to admit that fast development of distant education is the only way to save national intellectual capital. Introduction of distant education should create the alternative to traditional methods and become an important part of overall strategy of Russian national universities.